The Relationship between the Use of Edulearning and the Learning Outcomes of PAI and Ethics in Grade VIII Junior High School Students - hilmi, fuad (CV. Media Publikasi Profesional, 2024)
This study examines the relationship between the use of Edulearning and the learning outcomes of Islamic Religious Education (PAI) and Ethics in grade VIII students at Mekar Arum Junior High School. The background of the research is based on the increasing role of technology in education, although its implementation often faces obstacles, such as teachers' lack of understanding of technology and limited access by students. Using a qualitative approach and correlational methods, this study involved 206 students as subjects. The data shows that the average use of Edulearning is at a score of 3.8 (scale 1-5), with an average learning outcome of 78.5 (scale 0-100). The majority of students achieved the